2019
DOI: 10.1523/eneuro.0431-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Cells in the Rodent Olfactory Bulb Resemble Non-Bursting Superficial Tufted Cells and Are Primarily Inhibited upon Olfactory Nerve Stimulation

Abstract: The intrinsic vasopressin system of the olfactory bulb is involved in social odor processing and consists of glutamatergic vasopressin cells (VPCs) located at the medial border of the glomerular layer. To characterize VPCs in detail, we combined various electrophysiological, neuroanatomical, and two-photon Ca 2+ imaging techniques in acute bulb slices from juvenile transgenic rats with eGFP-labeled VPCs. VPCs showed regular non-bursting firing patterns, and displayed slower membrane time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 88 publications
(142 reference statements)
4
41
0
Order By: Relevance
“…For OB projection neurons, however, only little information about chemotypes is available at this point: Pcdh1 and Tbx21 (Haddad et al, 2013;Nagai et al, 2005) have been shown to be selectively expressed in a subset of OB projection neurons. CCK distinguishes a subset of TCs (superficial TCs, (Liu and Shipley, 1994;Seroogy et al, 1985;Short and Wachowiak, 2019;Sun et al, 2020); vasopressin expressing cells might constitute a further subset of superficial TCs (Lukas et al, 2019). Heterogeneous expression of both the GABAa receptor as well as voltage-gated potassium channel subunits have been observed (Padmanabhan and Urban, 2010;Panzanelli et al, 2005), albeit not linked to specific cell types.…”
Section: Introductionmentioning
confidence: 99%
“…For OB projection neurons, however, only little information about chemotypes is available at this point: Pcdh1 and Tbx21 (Haddad et al, 2013;Nagai et al, 2005) have been shown to be selectively expressed in a subset of OB projection neurons. CCK distinguishes a subset of TCs (superficial TCs, (Liu and Shipley, 1994;Seroogy et al, 1985;Short and Wachowiak, 2019;Sun et al, 2020); vasopressin expressing cells might constitute a further subset of superficial TCs (Lukas et al, 2019). Heterogeneous expression of both the GABAa receptor as well as voltage-gated potassium channel subunits have been observed (Padmanabhan and Urban, 2010;Panzanelli et al, 2005), albeit not linked to specific cell types.…”
Section: Introductionmentioning
confidence: 99%
“…As we recently demonstrated [8] that ON stimulation alone primarily inhibits VPCs, we suggest that (1) olfactory social cues alone are insufficient to excite VPCs and (2) VPC excitation is driven or unlocked by non-olfactory, top-down social signals. To test this hypothesis, we chose urine as an isolated olfactory social cue [21] and a novel male juvenile rat as a complete social stimulus.…”
Section: Social Interaction Activates Bulbar Vpcsmentioning
confidence: 51%
“…Within the OT, middle tufted cells project to the lateral portion, whereas the medial portion is preferentially innervated by mitral cells ( Igarashi et al, 2012 ). Although it was previously undetermined if external tufted cells project their axons outside the OB ( Schoenfeld et al, 1985 ; Tobin et al, 2010 ; Lukas et al, 2019 ), Hirata et al (2019) recently showed that at least a subpopulation of external tufted cells do target the anterolateral edge of the OT as well as the pars externa of the AON.…”
Section: Similarities and Differences Between Mitral And Tufted Cellsmentioning
confidence: 99%
“…Thus, external tufted cells likely transmit the olfactory information to specific regions in the olfactory cortex with unique temporal patterns. On the other hand, vasopressin, a neuropeptide, is predominantly expressed by external tufted cells with secondary dendrites and some middle tufted cells, but not by mitral cells, in the rodent OB ( Tobin et al, 2010 ; Lukas et al, 2019 ). It is proposed that the vasopressin-positive external tufted cells are involved in mechanisms of social recognition via the odor signatures ( Dluzen et al, 1998a , b ; Tobin et al, 2010 ; Wacker et al, 2011 ).…”
Section: Similarities and Differences Between Mitral And Tufted Cellsmentioning
confidence: 99%
See 1 more Smart Citation